Теоретичний базис формування механізму регулювання фінансової безпеки суб’єкта господарювання - Утенкова, Каріна; Utenkova, Karina (Дніпро : Дніпровський державний аграрно-економічний університет, 2024)
Стаття присвячена теоретичним аспектам формування механізму регулювання фінансової безпеки суб’єкта господарювання. Метою статті є подальший розвиток механізму регулювання фінансової безпеки суб’єкта господарювання в умовах ризиків та невизначеностей. Для вирішення визначених завдань у процесі дослідження використано загальнонаукові та спеціальні методи, а саме: діалектичний метод пізнання економічних явищ, принципи економічної теорії щодо сутності і змісту фінансової безпеки; методи теоретичного узагальнення та порівняння використовувались у процесі опрацювання літературних джерел та вивчення поставлених питань; абстрактно-логічний для теоретичного узагальнення висновків та аналізу результатів дослідження. Уточнено сутність економічної категорії «фінансова безпека суб’єкта господарювання», обґрунтовано необхідність формування дієвого механізму регулювання фінансової безпеки суб’єктів господарювання. Розглянуто сутність механізму фінансової безпеки відповідно до теорії економічних механізмів (mechanism design theory). Охарактеризовано основні елементи механізму регулювання фінансової безпеки. Зазначено, що основними завданнями механізму регулювання фінансової безпеки є: забезпечення сталого економічного розвитку суб’єкта господарювання, досягнення бажаного рівня ключових показників його діяльності; захист від негативного впливу зовнішніх і внутрішніх загроз; забезпечення постійного моніторингу стану фінансової безпеки; формування надійних інформаційних потоків і своєчасне забезпечення зацікавлених осіб інформацією про фінансовий стан суб’єкта господарювання; запобігання небезпекам і загрозам у діяльності, а також можливість їх локалізації і ліквідації.

The article is devoted to the theoretical aspects of the formation of a mechanism for regulating the financial security of a business entity. In the conditions of martial law, caused by military aggression on the part of the russian federation, the financial security of business entities has received new challenges and threats, the mechanisms for countering which have not yet been fully developed. The purpose of the article is the further development of the mechanism for regulating the financial security of the economic entity in conditions of risks and uncertainties. In order to solve the identified tasks, general scientific and special methods have been used in the research process, including: the dialectical method of understanding economic phenomena, the principles of economic theory regarding the essence and content of financial security; methods of theoretical generalization and comparison have been used in the process of processing literary sources and studying questions; abstract-logical for theoretical generalization of conclusions and analysis of research results. The essence of the economic category "financial security of a business entity" has been specified, the necessity of forming an effective mechanism for regulating the financial security of business entities has been substantiated. The essence of the mechanism of financial security is considered in accordance with the theory of economic mechanisms (mechanism design theory). The main elements of the regulation mechanism of financial security are characterized. The financial security regulation mechanism is a key component of the economic security system, which is a set of legally regulated methods, measures, tools, and levers that, in interaction, ensure the implementation of the financial development strategy of the business entity. It is noted that the main tasks of the financial security regulation mechanism are: ensuring sustainable economic development of the business entity, achieving the desired level of key indicators of its activity; protection against the negative impact of external and internal threats; ensuring constant monitoring of the state of financial security; formation of reliable information flows and timely provision of interested persons with information about the financial condition of the business entity; prevention of dangers and threats in the activity, as well as the possibility of their localization and elimination.
Theoretical basis for the formation of the mechanism for regulating the financial security of the business entity
Keywords: SOCIAL SCIENCES::Business and economics; фінансова безпека; суб’єкт господарської діяльності; складові механізму фінансової безпеки; financial security; subject of economic activity